Associations of Ozone and PM2.5 Concentrations With Parkinson's Disease Among Participants in the Agricultural Health Study. Issue 5 (May 2015) - Kirrane, Ellen F.; Bowman, Christal; Davis, J. Allen; Hoppin, Jane A.; Blair, Aaron; Chen, Honglei; Patel, Molini M.; Sandler, Dale P.; Tanner, Caroline M.; Vinikoor-Imler, Lisa; Ward, Mary H.; Luben, Thomas J.; et al.
Abstract : Objective: This study describes associations of ozone and fine particulate matter with Parkinson's disease observed among farmers in North Carolina and Iowa. Methods: We used logistic regression to determine the associations of these pollutants with self-reported, doctor-diagnosed Parkinson's disease. Daily predicted pollutant concentrations were used to derive surrogates of long-term exposure and link them to study participants' geocoded addresses. Results: We observed positive associations of Parkinson's disease with ozone (odds ratio = 1.39; 95% CI: 0.98 to 1.98) and fine particulate matter (odds ratio = 1.34; 95% CI: 0.93 to 1.93) in North Carolina but not in Iowa. Conclusions: The plausibility of an effect of ambient concentrations of these pollutants on Parkinson's disease risk is supported by experimental data demonstrating damage to dopaminergic neurons at relevant concentrations. Additional studies are needed to address uncertainties related to confounding and to examine temporal aspects of the associations we observed.